Introduction and evaluation of the performance of Japanese Quail (Coturnix Coturnix Japonica) -A new component of homegardens in South Andaman - Venkatesh, A.; Choudhuri, N.C.; Kundu, A.; Medhi, R.P. (Indian Journal of Agroforestry, 2020)
To get additional income from the homegardens and ensuring employment opportunities to the family members, a new component viz., Japanese quail was introduced in 17 homegardens representing 9 villages in South Andaman. The adoptability, growth performance and economic returns were evaluated. A net profit of Rs. 4.51 per quail bird was obtained. The optimal unit size for more return will be 101-200 or 201-400 for the Island condition as a component of home garden.